2015
DOI: 10.1002/pi.4953
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive poly(vinylene carbonate)s based on reaction development patterning with dilute aqueous alkaline solution

Abstract: Pattern formation of copolymers containing vinylene carbonate units was achieved by reaction development patterning, in which permeation of the developer and hydrolysis of the carbonates were selectively induced at irradiated areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…[16][17][18][19][20] In the past few years, various POSS macromers have also been introduced into polyimides. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Tamaki et al 37 and Huang et al 38 first reported the preparation of POSS-containing hybrid polyimides by the use of an octafunctional POSS amine. Notably, the glass transition temperatures of the materials were dramatically enhanced whereas the coefficient of thermal expansion decreased.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] In the past few years, various POSS macromers have also been introduced into polyimides. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Tamaki et al 37 and Huang et al 38 first reported the preparation of POSS-containing hybrid polyimides by the use of an octafunctional POSS amine. Notably, the glass transition temperatures of the materials were dramatically enhanced whereas the coefficient of thermal expansion decreased.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a different type of patternforming method, reaction development patterning (RDP) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Pattern formation by RDP uses nucleophilic acyl substitution reaction between nucleophiles such as OH − in developer and carbox-ylic acid derivatives like imide and ester groups in polymer (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%